Bovine theileriosis in Malaysia - Fadzil, M.; Ragavan, K. (Persatuan Doktor Veterinar Malaysia, 1986)
Case records of 972 cattle and 113 buffaloes (Bubalus bubalis) kept at the Faculty of Veterinary Medicine and Animal Science, Universiti Pertanian Malaysia, from 1980-1984 were reviewed. Fifty eigh t cattle were naturally infected with Theileria orientalis, 24 of which had anaemia. Temperate breeds and their crosses appeared to be more susceptible to Theileria infection than the indigenous breeds.